FEATURES OF PROFESSIONAL FORMATION OF FUTURE TEACHERS OF ART SUBJECTS AESTHETIC CYCLE (Pedagogy of Higher and Secondary Education, 2004)
The article investigates the present today situation in terms of professional preparation of a future teacher as well as ways of effectively enhancing students’ professionalism at the art teachers department.